Effectiveness of vedolizumab dose intensification to achieve inflammatory bowel disease control in cases of suboptimal response. Issue 3 (11th July 2019) - Samaan, Mark A; Birdi, Siddharth; Morales, Maria Sierra; Honap, Sailish; Tamilarasan, Aravind Gokul; Cunningham, Georgina; Koumoutsos, Ioannis; Ray, Shuvra; Mawdsley, Joel; Anderson, Simon H C; Sanderson, Jeremy; Irving, Peter M
Abstract : Background: Despite the proven efficacy of vedolizumab (VDZ) for ulcerative colitis (UC) and Crohn's disease (CD), suboptimal response is commonly encountered. However, data regarding the effectiveness of dose intensification (by interval shortening) to achieve response are limited. Objectives: We evaluated the effectiveness of dose intensification at achieving response in patients with a previously suboptimal response to VDZ. Additionally, we aimed to identify predictors of response to this strategy. Methods: We performed a retrospective cohort study of patients who underwent VDZ dose intensification for suboptimal response. Clinical disease activity was evaluated at the point of dose intensification (baseline) and at weeks 12 and 24. Response was defined as Harvey-Bradshaw Index (HBI) or Simple Clinical Colitis Activity Index (SCCAI) reduction of ≥3, and remission as HBI <5 or SCCAI <3. Results: A total of 36 patients received dose intensification to 4-weekly infusions: 18 CD, 14 UC and 4 inflammatory bowel disease-unclassified (analysed in the UC group). Median SCCAI scores fell from 6 (range 0–11) at baseline to 4 (0–6, p=0.008) at week 24, while HBI scores did not change significantly (4 (0–27) and 3 (0–8), p=0.092). Overall median C reactive protein (CRP) fell from 6 mg/L (1–23) to 2 mg/L (1–17, p=0.011). Of 20 patients with clinically active disease at baseline, 10 (50%) responded, of whom 4 (20%) achieved remission at week 24. Univariate analysis demonstrated low baseline CRP (p=0.045) and response at week 12 (0.020) were associated with week 24 response. Conclusions: Our findings demonstrate VDZ dose intensification to be effective at achieving clinical response in half of patients. Low baseline CRP and response at week 12 are potential predictors of week 24 response.